High-Resolution Three-Dimensional Imaging of Neurovascular Conflicts on 3 Tesla MRI - Sharma, Vidushi; K.S. Vedaraju; Khatoon, Neha (Asian Journal of Medical Radiological Research, 2022)
Background: Neurovascular conflict is a path anatomical phenomenon which is primarily idiopathic however there is implication of compression by vessels causing mechanical irritation of the nerve. Cranial nerve neuralgia is characterised by paroxysmal attacks of pain or abnormal movements in the distribution of the affected nerve. Most common are trigeminal neuralgia and hemifacial spasm. In this study,the emphasis is on the role of Three dimensional fast imaging employing steady state acquisition (3D FIESTA-C) sequence in detecting, localizing and grading of various NVC in approximately 30 suspected patients. Subjects and Methods: This Hospital-based prospective study consists of 30 patients who were clinically suspected to have Neurovascular conflict over a 2-year period extending from January 2021 to January 2022 in department of radio diagnosis, Narayana Medical College, Nellore. Routine images were acquired along with 3D FIESTA-C sequence in 3 tesla MRI scanner. Results: Amongst 30 patients, 20 were included in the study with mean age of presentation being 49 years and female: male ratio of 1.5. On imaging most common nerve involvement observed in this study was Trigeminal (50%), followed by Facial (30%), Vestibulocochlear (15%) and Optic nerve (5%). The offending arteries seen were AICA in 40% cases, SCA in 35%, PCA, VA and ICA in 5% cases each. IN 20 cases, Grade I conflict is observed most frequently in 13 cases, Grade II in 4, and Grade III in 3. Conclusion: Non-invasive evaluation and anatomical characterization of cranial nerves can be carried out by three dimensional FIESTA-C sequence in MRI. It also aids in correct diagnosis establishment and providing proper guidance in neuroanatomy for neurosurgical decompression procedures thus in turn improving the outcome for patients.